Pengaruh Self Esteem terhadap Body Image Remaja Akhir Putri Pengguna Tiktok - Alika Salsabila Rahma Suhardian; Siti Qodariah (UNISBA Press, 2022)
Abstract. Post-pandemic conditions make teenagers more at home and there is an increase in accessing the internet and social media. Currently, Tiktok application is the most popular and in-demand application among teenagers. The city of Bandung is the city with the tiktok in West Java.application tiktok has a lot of content and features that can be played, displayed, and enjoyed by its users. One of the content in tiktok is beauty and fashion content where in this content users are presented and facilitated to contain content regarding their own beauty by appearing on the For Your Page (FYP) tiktok.existence of beauty and fashion that is in great demand among teenagers raises the ideal self so that the term